Code-Mixing in WhatsApp Group Discussions of Online English Classes - Rahmawati, Lina; Sholeha, Mar'atus; Rizka, Haira (English Education Department, Universitas Islam Indonesia, 2022)
The COVID-19 pandemic has forced the educational world to switch from offline classes to online classes. Limited access to the internet has encouraged many people to use WhatsApp to teach instead of academic platforms. Although WhatsApp is not designed for educational purposes, many teachers prefer using it to conduct online discussions, including in English classes. This new model of communication using WhatsApp for English classes has resulted in the interesting phenomenon of code-mixing. This paper aims to investigate the types and functions of code-mixing used in WhatsApp groups of online English classes. This study employed a qualitative method. The sample of this research was conversations between the lecturers and students in WhatsApp group chats of online English classes during the pandemic. The data were collected through observation. The collected data were then analyzed by using textual analysis. This study revealed three types of code-mixing used in online English classes on WhatsApp group chats: insertion, alternation, and congruent lexicalization. Next, this study found five functions of code-mixing in online English classes on WhatsApp group chats: quotation, address specification, interjection, message qualification, personalization, and objectification. Address specification, personalization, and objection were dominantly found because specific sentences frequently refer to people, things, or arguments during discussions on WhatsApp group chats.